Association between carotid artery and abdominal aortic aneurysm plaque. Issue 1 (December 2015) - Raz, Eytan; Anzidei, Michele; Porcu, Michele; Bassareo, Pier; di Martino, Michele; Mercuro, Giuseppe; Saba, Luca; Suri, Jasjit
Abstract Background The correlation between AAA and carotid artery plaque is unknown and a common etiology and pathophysiology is suspected by some authors. The purpose of this work was to explore the association between the features of a) carotid artery plaque and b) abdominal aortic aneurysm (AAA) plaques using multi-detector-CT Angiography (MDCTA). Methods Forty-eight (32 males; median age 72 years) patients studied using a 16-detectors CT scanner were retrospectively analyzed. A region of interest (ROI) ≥ 2 mm2 was used to quantify the HU value of the plaque by two readers independently. Inter-observer reproducibility was calculated and Pearson correlation analysis was performed. Results The Bland-Altman plots showed the inter-observer reproducibility to be good. The Pearson correlation was 0.224 (95 % CI = 0.071 to 0.48), without statistically significant association between HU measured in the carotid artery plaque and in the AAA plaques (p  = 0.138); after exclusion of the calcified plaques from the analysis, the rho values resulted 0.494 (95 % CI = 0.187 to 0.713) with a statistically significant association (p  = 0.003). Conclusion In this study, we found an association between the features of the non calcific carotid plaque and the features of AAA plaque.